Health information ties: preliminary findings on the health information seeking behaviour of an African-American community - Ophelia T. Morey (Information Research: An International Electronic Journal)
Introduction. The purpose of this study is to explore the health information seeking behaviour of African-Americans using Granovetter's strength of weak ties as the theoretical framework. Method. A listed household (LHH) telephone survey of 216 residents who reside on the Near East Side of Buffalo, New York. Using the Rand() feature in MS Excel a random sample was drawn from the LHH telephone numbers that were randomly selected from census tracts covering the target area in Buffalo, New York. Random samples were drawn three times until at least 200 telephone surveys were completed. Analysis. Data analysis was completed using SPSS 13.0 for Windows. Both bivariate and multivariate analyses were performed along with analyzing descriptive statistics and chi-square to determine the association between the source of health information as related to demographics and tie strength between individuals. Results. Overall, most respondents rely on a health service professional for health information (45.5%) followed by a web site (14.1%). Respondents reported having a 'somewhat close' (significant tie) relationship with health care professionals as compared to having a 'very close' (core tie) relationship with family members. The importance of health service professionals as a significant or weak tie in health information seeking is consistent with the strength of weak ties theory. Results on proxy searching behaviour or searching on behalf of another person are also examined. Most respondents sought information for themselves (76.2%), although 22.2 percent sought health information on behalf of another person. Conclusion. : These findings confirm the important role of health service professionals (weak tie) in health information seeking by underserved populations and suggest the need for investigation on the information giving behaviour of these professionals. These findings also demonstrate the need for further research on strong ties or close family and friends as a source of health information and in particular their role in proxy health information behaviour.